2021
DOI: 10.7759/cureus.18791
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Regarding Risk of Diabetic Foot Among Diabetic Patients in Aseer Region, Saudi Arabia

Abstract: BackgroundDiabetic foot care is vital as it is preventable complication but dangerous even a small trauma can end with serious consequences. Diabetes may cause nerve damage that affects feet sensation. Diabetes may also reduce blood flow to the feet, making it harder to heal an injury or resist infection. Because of these problems, patients may lose notice of early foot abnormalities. Diabetic patients' awareness regarding how to care for their feet plays a significant role in preventing these complications. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…As for the results of the Saudi study, the percentage was estimated at 65%. ( 23) In our study, most of the participants with a percentage of 74% were not committed to the calibration of hemoglobin and this is consistent with two studies, the rst was conducted in Saudi Arabia and the other was conducted in Jordan with a rate of 70%.49. (26) Different rates of diabetes complications were observed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As for the results of the Saudi study, the percentage was estimated at 65%. ( 23) In our study, most of the participants with a percentage of 74% were not committed to the calibration of hemoglobin and this is consistent with two studies, the rst was conducted in Saudi Arabia and the other was conducted in Jordan with a rate of 70%.49. (26) Different rates of diabetes complications were observed.…”
Section: Discussionsupporting
confidence: 89%
“…Poor control of diabetes, prolonged uncontrolled diabetes, peripheral vasculopathy, aging, and poor awareness regarding diabetes in general and foot care in particular are some of the most well-known risk factors for foot sugar. (23) The results of our study showed that 54% of the patients were male. Similar to the nding of male sex predominance in diabetic patients where the effect of sex on foot ulcers has been controversial, it has been shown that gender may pose a signi cant risk factor for ulcer development.…”
Section: Discussionmentioning
confidence: 62%
“…One of the previous studies found (72%) had intermediate knowledge, (13.3%) had good knowledge, and (14.7%) had poor knowledge (Al-Aboudi et al, 2016). Another previous study found that more than two-thirds of diabetic patients were knowledgeable about diabetic foot management (67.4%), the remaining have poor knowledge (32.6%) (Al Amri et al, 2021). Another study revealed that (53.3%) of the sample had moderate knowledge, while insufficient knowledge represented (46.7%) (Alhuqayl et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…The answer including Yes was scored as (2) and No was scored as (1). The used questionnaire are adopted and developed from several scientific researches (Tork & Elgazzar, 2020), (Al Amri et al, 2021), (Taksande et al, 2017), (Magbanua & Lim-Alba, 2017), (Al-Hariri et al, 2017).…”
Section: Study Instrumentmentioning
confidence: 99%
“…Old age, diabetes duration, and hypertension are just a few of the diabetic foot's risk factors. The primary risk factors for foot ulcers and eventually amputation are peripheral neuropathy involving sensory loss and peripheral vascular disease with ischemia (14).…”
Section: Discussionmentioning
confidence: 99%